Economy, development and human rights in Boyacá, Colombia 1990-2010 - Estupiñán, Joan Tejedor; Estupiñán, Ricardo Tejedor (Universidad Pedagógica y Tecnológica de Colombia, 2013)
In the last two decades, the model of neoliberal political economy adopted in Colombia, has had an impact on development and economic, social and cultural rights of the inhabitants of Boyacá. This problem is studied from the relationship between economic growth and development in Boyacá, the importance of development plans and the budget problemof the department is analized. Finally it describes as the neoliberal model does not generates sustainability, development, and respect for its inhabitants rights. We made a critical analysis of sources such as interviews, statistical reports of governmental and non-governmental institutions, newspaper and magazine articles, books, chapters, documents and bibliographic databases on the Internet.